Non-accidental trauma causing inferior vena cava and liver injuries - Mary E. Stuckey; Muhammad Owais Abdul Ghani; Amber Greeno; Harold N. Lovvorn; Melissa E. Danko (Elsevier, 2020)
Child abuse, or non-accidental trauma (NAT), resulting in concomitant hepatic and inferior vena cava (IVC) injuries is exceedingly rare. No cases of survival after physical abuse giving rise to concurrent hepatic and IVC injuries have been reported in the current literature. This disturbing case details the presentation and hospital course of a 3-year old male who sustained grade V hepatic injury and disruption of the IVC secondary to NAT. The patient was referred from another hospital for evaluation and management of altered mental status and evolving hemodynamic instability. Large volume fluid was discovered on abdominal ultrasound, suggestive of hemoperitoneum. Subsequent comprehensive trauma survey raised suspicion for physical child abuse, and computed tomography (CT) scan revealed a grade V hepatic injury with complex IVC disruption. Mass transfusion protocol (MTP) was activated, and the patient underwent immediate damage control laparotomy. Coagulopathy, acidosis, and hypothermia were corrected within 4 hours of surgery. Two subsequent abdominal explorations were performed over the next 36 hours. Despite massive hemorrhage, disseminated intravascular coagulopathy (DIC), and respiratory failure, the patient survived and achieved complete neurologic recovery. The National Trauma Data Bank (NTDB) was queried for similar hepatic and caval injuries after child abuse, and only one patient was found who did not survive.